Synthesis and characterization of a novel activated carbon-supported cobalt catalyst from biomass mixture for tetracycline degradation via persulfate activation - Erdem, Hatice; Erdem, Mehmet (Springer Heidelberg, 2022)
In this study, a new activated carbon (AC)-supported Co-based catalyst was synthesized from a biomass mixture by single-step pyrolysis for tetracycline (TC) degradation with persulfate (PS). The catalyst was characterized by BET-surface area, total pore volume, pore size, SEM, EDS, XRD, and VSM analysis. Its catalytic performance in the oxidative TC degradation was investigated depending on catalyst dosage, PS concentration, contact time, pH, and co-existing anion. The results show that the catalyst has 515.46 m(2)/g surface area, 0.2661 cm(3)/g pore volume, 79.14% C, and 14.63% Co. The catalyst exhibited high catalytic activity in oxidative degradation of TC with PS. One hundred percent mineralization could be achieved at the conditions of 0.5 g/L of catalyst dosage, 1 mM PS, pH 5.88, and 45 min. Quenching tests showed that the catalyst successively activated PS to generate SO(4)(center dot-)and OH center dot. However, SO(4)(center dot-)was identified as the main oxidizing radical in TC degradation. TC degradation was found to fit to first-order kinetics. The activation energy of the reaction was calculated to be 7.095 kJ/mol. Unlike conventional impregnation and precipitation methods applied for AC-supported catalyst synthesis, a superior catalyst can be obtained from cheap and abundant biomasses and Co-salt by a single-step pyrolysis. The high catalytic performance of the catalyst and short degradation period show that it can be a promising catalyst for degradation organic pollutants with PS.
Keywords: Catalyst synthesis; Tetracycline; Biomass; Degradation; Heterogeneous catalysis